Pengembangan Media Ajar Interaktif Berbasis Pop Up Book Dalam Memahami Kisah Keberanian Nabi Ibrahim AS - Aulia Rahma; Anita Puji Astutik (Jurnal Teknologi Pendidikan, 2026)
This study aims to determine the Learning about the exemplary stories of the prophets is often trapped in a conventional, one-way pattern of delivery, so that students often fail to grasp the deeper meaning of the stories being told. This situation calls for innovative teaching media that not only convey information, but also stimulate emotional engagement and instill spiritual values. This study developed interactive teaching media based on Pop Up Books, focusing on the story of the courage of Prophet Ibrahim AS, which presents a series of two-dimensional visuals, interactive mechanisms, and a narrative flow designed to provide a more immersive learning experience. The Pop Up Book consists of a series of illustrative pages that display important moments in the journey of Prophet Ibrahim AS. Each visual display is designed with interactive elements so that it can foster curiosity, strengthen understanding, and provide emotional depth to students. This teaching medium not only serves as a learning tool, but also as a creative innovation that combines cognitive, affective, and psychomotor aspects into a unified learning experience.  With an immersive visual approach, this Pop Up Book is able to engage students more and enable them to emulate the values of courage from the story of Prophet Ibrahim AS in their daily lives